Perancangan Sistem Transfer Daya Nirkabel untuk Unmanned Aerial vehicle (UAV) Micro Jenis Quadcopter - Setyawan Wahyu Pratomo (Jurusan Teknik Elektro Universitas Andalas, 2016)
In the Unmanned Aerial Vehicle ( UAV ) type of Quadcopter, the source of power supply in form of a battery that is only able to work 10-15 minutes in the air is a own issue for the performance of Quadcopter. While the performance of quadcopter at a high that are difficult to reach, it is expected over the role an operator must manually connect the charging cable to battery can be replaced by the system automatically when battery runs out. For that, in this paper discusses design of wireless power transfer system for Quadcopter to charge battery without the help of an operator and not to be done landfalls on the ground. The recharging process of battery can be done at the top of the building or in the common ground that has been installed wireless power transfer. The aim is to improve the performance of quadcopter`s work in the air in accordance with the usefullness. From the design of wireless power transfer system for quadcopter`s charging the battery obtained the results the best efficiency power transfer is 62.24 % with effective distance 10cm. The frequency`s system obtained from an Oscillator Colpitss 333,1KHz by implementing the principles of electromagnetic induction.Keywords : Quadcopter, charging battery,electromagnetic inductionAbstrak— Dalam Unmanned Aerial Vehicle ( UAV ) jenis Quadcopter, sumber catu daya berupa baterai yang hanya mampu bekerja 10-15 menit di udara merupakan permasalahan tersendiri bagi performa Quadcopter. Sedangkan perfomansi dari Quadcopter pada ketinggian yang susah dijangkau, diharapkan peran operator yang selama ini harus mengkoneksikan secara manual kabel charging ke baterai bisa digantikan oleh sistem secara otomatis ketika baterai akan habis. Untuk itu dalam paper ini membahas suatu perancangan sistem transfer daya nirkabel untuk Quadcopter mengisi ulang baterai tanpa bantuan operator dan tidak harus dilakukan pendaratan di atas tanah. Proses isi ulang ( charging ) baterai bisa dilakukan di atas gedung maupun di landasan yang telah terpasang transfer daya nirkabel. Tujuannya adalah meningkatkan performansi kerja Quadcopter di udara sesuai dengan kegunaanya. Dari perancangan sistem transfer daya nirkabel untuk Unmanned Aerial Vehicle ( UAV ) jenis Quadcopter mengisi ulang ( charging ) baterai, diperoleh hasil efisiensi transfer daya terbaik sebesar 62,24% dengan jarak efektif 10 cm. Frekuensi sistem transfer daya nirkabel diperoleh dari rangkaian Colpitss Oscillator sebesar 333,1 KHz dengan menerapkan prinsip induksi elektromagnetik.Kata Kunci : Quadcopter, charging baterai, induksi elektromagnetik